2018
DOI: 10.1039/c8ta00822a
|View full text |Cite
|
Sign up to set email alerts
|

Complex hydrides as thermal energy storage materials: characterisation and thermal decomposition of Na2Mg2NiH6

Abstract: The thermodynamic properties of Na2Mg2NiH6 have been investigated to determine feasibility as a thermal energy storage material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Experimental results showed that the decomposition of Na 2 Mg 2 FeH 8 is a three‐stage reaction with dehydrogenation enthalpies of 93, 87, and 111 kJ mol −1 ‐H 2 , respectively . The decomposition of Na 2 Mg 2 NiH 6 , on the other hand, is a two‐step reaction with the overall dehydrogenation enthalpy of 94 kJ mol −1 ‐H 2 , and can be operated in the temperature range of 318–568 °C under H 2 pressures from 1 to 150 bar . Light metal complex hydrides such as alanates, borohydrides and amide–hydride composites can also be used as thermal energy storage materials.…”
Section: Thermal Energy Storagementioning
confidence: 99%
“…Experimental results showed that the decomposition of Na 2 Mg 2 FeH 8 is a three‐stage reaction with dehydrogenation enthalpies of 93, 87, and 111 kJ mol −1 ‐H 2 , respectively . The decomposition of Na 2 Mg 2 NiH 6 , on the other hand, is a two‐step reaction with the overall dehydrogenation enthalpy of 94 kJ mol −1 ‐H 2 , and can be operated in the temperature range of 318–568 °C under H 2 pressures from 1 to 150 bar . Light metal complex hydrides such as alanates, borohydrides and amide–hydride composites can also be used as thermal energy storage materials.…”
Section: Thermal Energy Storagementioning
confidence: 99%
“…Also the interest towards metal hydrides is not recent, these thermochemical storage systems were explored since the mid-1970s [264]. Several applications and different metal hydrides systems were explored for thermochemical heat storage [265][266][267][268][269].…”
Section: Thermochemical Processes and Materialsmentioning
confidence: 99%
“…In addition, a splitting of the NaH Bragg peaks is observed to occur above 100 °C which is associated with the dissolution of NaOH impurities into the NaH lattice. 11 From TGA, the mass loss in the first decomposition step was measured as 16.8 %, while quantitative Rietveld refinement determined that 85 wt% of NH4Cl has been consumed along with 100 % NaH, giving a weight loss of 16% consisting of 0.85NH3 and 0.925H2. The remaining NH4Cl decomposes in an endothermic process, with a maximum rate of H2 and NH3 release at ~215 °C, leaving NaCl as the only crystalline product.…”
Section: Thermal Decomposition Of Pure Nh4clmentioning
confidence: 99%
“…They have the capacity to be developed from inexpensive or abundant materials such as sodium, magnesium, calcium and titanium and form a variety of hydrogen containing species including ionic hydrides, complex hydrides and interstitial hydrides. [7][8][9][10][11] The thermal energy density of metal hydrides is up to thirty times more than molten salts, currently used to store solar energy. 3,12,13 They also have the potential to reversibly absorb large amounts of hydrogen which makes them ideal for fuel cell applications.…”
Section: Introductionmentioning
confidence: 99%